Business English: the Quintessence of the Corporate World - Abilasha, R.; Ilankumaran, M. (International Journal of Engineering and Technology, 2018)
The status of English in the global arena has become an irreplaceable and unparalleled one. The language has become apparent and prominent in the key aspects of trade and commerce for the last two decades or more. Though the first spread of the language was due to colonial expansion, it has attained a level of being considered a standard and common one for all official communications by and large particularly in the countries where a vast number of regional and native languages are spoken. English, indeed, is not the most widely spoken language on the earth if it is taken in terms of number of native speakers. It has become a prominent language as it is spoken by people around the world – 350 million of 6 billion people. In case of International business, it is the only language that has occupied a great space revealing the importance of the language. This paper brings to light how English as a language is used for business communication in the corporate sectors. The business at global level is conducted across borders of countries with English as a principal language. The use of language provides many benefits such as helping the concern grow and succeed, invigorating trust among colleagues and clients,  strengthening the relationship with everyone in and out the concern, escalating the skill set of individuals along with commanding lucrative packages and embellishing the international relationship by means of cultural understanding.